dwt 2017
DOI: 10.5004/dwt.2017.0449
|View full text |Cite
|
Sign up to set email alerts
|

Removal of pharmaceutically active compounds by using low-pressure membrane processes

Abstract: García-Ivars, J.; Iborra Clar, MI.; Massella, M.; Carbonell Alcaina, C.; Alcaina-Miranda, MI. (2017). Removal of pharmaceutically active compounds using low-pressure membrane processes. Desalination and Water Treatment. 69:252-260. doi:10.5004/dwt.2017 ABSTRACTThe increasing demand on water resources throughout the world has motivated researchers to seek new ways to obtain quality water increasing their interest in water reclamation. However, the presence of harmful organic chemicals such as pharmaceuticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…However, its application in the elaboration of asymmetric membranes for ultrafiltration is limited by the inherent hydrophobic properties and the difficulty to dissolve it and form the asymmetric structure . Several alternatives used to increase the hydrophilicity of a polymer surface have been reported; such as graft polymerization by UV irradiation, plasma modification, random copolymerization, and ion‐beam irradiation . Although these methods have achieved good results in improving hydrophilicity, they show low adhesion and stability on the polymer surface .…”
Section: Introductionmentioning
confidence: 99%
“…However, its application in the elaboration of asymmetric membranes for ultrafiltration is limited by the inherent hydrophobic properties and the difficulty to dissolve it and form the asymmetric structure . Several alternatives used to increase the hydrophilicity of a polymer surface have been reported; such as graft polymerization by UV irradiation, plasma modification, random copolymerization, and ion‐beam irradiation . Although these methods have achieved good results in improving hydrophilicity, they show low adhesion and stability on the polymer surface .…”
Section: Introductionmentioning
confidence: 99%
“…32 Three different experiments were conducted and the average value was reported. From the dry weight (M dry ) and wet weight (M wet ) of membranes, porosity (ε) 33 and equilibrium water content (EWC) 34 were measured for structural the stipulation of plain and hybrid membranes using following equations:…”
Section: Membrane Characterizationmentioning
confidence: 99%
“…Three different experiments were conducted and the average value was reported. From the dry weight ( M dry ) and wet weight ( M wet ) of membranes, porosity (ε) 33 and equilibrium water content (EWC) 34 were measured for structural the stipulation of plain and hybrid membranes using following equations: ε0.25em()%=MwetMdryA0.25eml0.25emρw0.25em×100 EWC0.25em()%=MwetMdryMwet×100 where A , ρ w and l are representing the membrane surface area (cm 2 ), water density (g/cm 3 ), and membrane thickness (cm), respectively. The thickness of the all dry membrane is in the range of 0.07–0.09 mm.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…Yoon et al [47] confirmed the rejection of hydrophobic organic micropollutants caused by adsorption onto UF membranes. Garcia-Ivars et al [48] observed that highly soluble pharmaceuticals (e.g., CF) showed low rejection values (~15%) during ultrafiltration.…”
Section: Hybrid Membrane Processesmentioning
confidence: 99%